Inability to Perform Retrograde Ureteroscopic Stone Treatment: A Postoperative Anatomical Change After Fleur-de-Lis Abdominoplasty - Parker L. Heger; Thomas F. Rashid; Lucas B. Vergamini; Bristol B. Whiles; Aaron Tverye; Wilson R. Molina (Case Reports in Urology)
Abdominoplasty is a frequently performed elective procedure, often indicated for patients after substantial weight loss resulting in significant redundant skin. Closing techniques and the lifting of the mons pubis during abdominoplasty have been proposed to alleviate symptoms of stress urinary incontinence by elevating and supporting the urethra. Despite these observations, the impact of abdominoplasty on pelvic anatomy and subsequent endoscopic procedures remains underexplored and underreported. We present a case where cystoscope passage as part of endoscopic laser lithotripsy for nephrolithiasis was impeded by altered anatomy in a patient with a history of Fleur-de-Lis abdominoplasty.